(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
Until now, there is no unity of views of maxillofacial surgeons on the problem of preserving teeth located in the area of cystic formation. This article presents a study of 24 patients hospitalized for small root apex cysts in the upper jaw. After the operation in the main group of patients, the residual bone cavity was filled with an osteoplastic preparation and autoplasma of blood, which showed significant advantages over traditional methods of treating cysts in the root part of the teeth in the maxillae.